PERALIHAN NAMA DESA MENJADI KAMPUNG DI KABUPATEN SIAK BERDASARKAN PERATURAN DAERAH KABUPATEN SIAK NOMOR 1 TAHUN 2015 TENTANG PERUBAHAN PENAMAAN DESA MENJADI KAMPUNG - Didik Saputra; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
There are several important reasons why the village was changed penyebutannya into villages, namely: In Philosophical, to restore or revive the old culture that Siak Malay culture; In Sociological, to change the paradigm that the village was not an underdeveloped area or behind because Siak itself is one of the areas with the greatest development in Indonesia, particularly in Riau; and In juridical, is the mandate contained in the Act No. 6 Year 2014 about the village, where the local knowledge of the cultural values of the area. So, with the change in the naming of the village into the village is also changing government administration, government structure, elements of regional programs, and so forth.This type of research is classified as socio-juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in the District of Lubuk In Siak, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this research with interviews, questionnaires, and review of the literature.The research problems are, among others: first, What is the urgency of transitional name of the village into a village in Siak Regency Regional Regulation Siak District No. 1 of 2015 on the Amendment Naming Village Being Kampung, second, How implications of switchover name of the village into a village in Siak based Siak District Regulation No. 1 Year 2015 on the Amendment Naming Being Kampung Desa. Results of the study are: first, in the Philosophical to restore or revive the old culture that Malay culture Siak, in Sociological to change the paradigm of society or human that the village was not a lagging regions and to preserve returned norms in society that is almost gone because eroded by the times, by Juridical to implement the mandate contained in the Act No. 6 of 2014 About the village, namely concerning their local knowledge should be developed in order to raise the existing culture in the area for each region, second, changing the nomenclature of Government Institutions from the village into the village, the adjustment Attributes Government which include letterhead, signpost names, banners, stamps, etc., necessary adjustment to the service of public Administration for the people of Kampung among others, the Family Card (KK), Identity Card (KTP), deed, and so forth.Keywords: Transition - The village - Kampung